Gift and gain : how money transformed Ancient Rome - Coffee, Neil (Classical culture and society, 2017)
'Gift and Gain' shows how, over the course of Rome's classical era, a vibrant commercial culture progressively displaced traditional systems of gift giving that had long been central to Rome's material, social, and political economy, with effects on areas of life from marriage to politics